Dominican scenes of the republican school in the exile, 1939-1945 - Alfonseca Giner de los Rìos, Juan Bernardo (Historia y Memoria de la Educación, 2019)
This paper describes the participation of Spanish refugees in Dominican education between 1939 and 1945, during which time almost 4,000 exiles arrived in the Dominican Republic . It is a preliminary study that seeks, on the one hand, to add to our knowledge of the impact and the work of the Spanish Republicans in the country, bringing to light references about the schools they established ―which totalled 29 and not 6, as was believed― as well as an appreciation of their participation in the Dominican school system. We also attempt to understand the processes of sociocultural appropriation of the republican school in exile that took place in the Dominican society of the time.